Analysis of the Effect of Fiscal and Monetary Policy on Economic Growth in Indonesia Pre and Post Covid-19 - Wartoyo Wartoyo; Nur Haida; Asni Komalasari; Alya Fauzi Zaizafun (JURNAL PROFIT, 2024)
AbstractThis study aims to determine the influence of fiscal policy and monetary policy on economic growth in Indonesia in 2007-2022. The independent variables used in this study are categorized into two camps, namely the fiscal policy camp consisting of tax revenue (X1) and government expenditure (X2). Meanwhile, monetary policy consists of interest rates (X3) and money supply (X4). This research uses data series obtained from the Central Statistics Agency (BPS) and Bank Indonesia (BI). In this study using quantitative methods and using multiple linear regression analysis. The results showed that the variable of tax revenue (X1) has a positive and significant effect on economic growth, government spending (X2) has a negative and significant effect on economic growth in Indonesia and interest rates (X3) have a negative and insignificant effect on economic growth in Indonesia, while the money supply (M2) has a positive and significant effect on economic growth.Keywords: Fiscal Policy, Monetary Policy and Economic Growth.